DESIGNING A MENTAL HEALTH EDUCATION PROGRAM TARGETED TOWARDS ADOLESCENTS IN RURAL VILLAGES - Suroso, Suroso; Aziz, Firman; Marzuki, Marzuki (PT Altin Riset Publishing, 2024)
The objective of this study is to create a mental health education program specifically designed for rural areas and assess its influence on the knowledge and attitudes of teenagers regarding mental health. The study methodology utilized is a developing approach that incorporates both qualitative and quantitative data analysis. Data were gathered via interviews, observations, and questionnaires both prior to and during engagement in the program. The research findings demonstrate that the program effectively enhanced teenagers' understanding of mental health and transformed their attitudes towards mental diseases, fostering greater empathy and support. The significance of these findings emphasizes the necessity of creating mental health education initiatives that are suitable for rural environments. Additionally, further investigation is required to evaluate the program's long-term efficacy and the factors that contribute to its successful execution. Therefore, this research provides a significant contribution to the endeavors aimed at improving the mental well-being of adolescents in rural regions.